A Study on the Stability of Different Frusemide Liquid Dosage Formulas: Oral Solution, Syrup, Elixir, Suspension and Emulsion - Fatima J. Jawad (College of Pharmacy University of Baghdad, 2017)
The present study aim at preparing frusemide in liquid form suitable for oral use. This is achieved through preparing different liquid forms of frusemide. The frusemide liquid is prepared in the following forms: oral solution, syrup and elixir with intensity of 1, 0.4 and 0.8% weight /volume respectively and in combination with potassium carbonate, polysorbate 80, alcohol and phosphate buffer solution of pH8 to dissolve the frusemide in the above mentioned forms. The different forms of the prepared medicine have been stored in glass bottles that can provide protection against light and at 40, 50, 600C for four months. Besides the pH has been checked to decide the period of validity. The results show that the expiration date of frusemide have lasted for 1.8, 1.07 and 1.22 years respectively for the oral solution, the syrup and the elixir. The suspensions of frusemide are formulated in combination with the following: polyvinyl pyrolidine, xanthan gum, the combination of (xanthan gum and sodium carboxymethyl cellulose), the combination of (xanthan: methyl cellulose) and chitosan.  The formulas which give suitable release of the drug are chosen for assessment according to the following considerations: The rat of sedimentation and apparent zero order degradation constant at 250C. In conclusion, it is found the best formula is that which includes poly vinylpyrolidine, tween20, glycerol, sorbitol, cocoa syrup and parabens at pH7. the fluidity of this chosen formula is psendoplastic type and its validity has lasted for about three years. The emulsion of frusemide is also prepared extemporaneously by using the commercial frusemide tablets in combination with acacia and olive oil. This should be consumed within 45 days of the date of production. Key word: frusemide, elixir, suspension, emulsion.